Analisis dan perencanaan aplikasi e-procurement untuk pengadaan barang dan jasa di PT Pertamina (Persero) - ABDULLAH, Catharina Susianti ([Yogyakarta] : Universitas Gadjah Mada, 2009)
This research was held to assist PT Pertamina (Persero) in organizing information system analysis and design of e-Procurement in procurement goods and services. We do hope that the result as system analysis and design would facilitate the decision making whether the information system development process would continue or not. This research using FAST (Framework for the Application of System Thinking) methodology to analyze and design. FAST provide a smart frame work and flexible that offer different type of project and strategy. The objective of this method is solving problems, observe the possibility and direction to start a project. Research use only five phase from seven phase existing, since this five phase have been presented the result of this research, such as primary investigation, problem analysis, requirement analysis, decision analysis, and design analysis. The result of this research provide a systematic flowchart e-Procurement system which present a design of systemic diagram integrated in procurement process and meet the requirement and user needs especially procurement function and Pertamina management which properly fit the Pertamina strategic plan stated in master plan existing. In addition to ensure the availability of information and data, this system be expecting to integrate with the existing application as MySAP.